2004
DOI: 10.1086/425215
|View full text |Cite
|
Sign up to set email alerts
|

The Anisotropy of Electron Magnetohydrodynamic Turbulence

Abstract: We present numerical studies of 3-dimensional electron magnetohydrodynamic (EMHD) turbulence. We investigate cascade timescale and anisotropy of freely decaying strong EMHD turbulence with zero electron skin depth. Cascade time scales with k −4/3 . Our numerical results clearly show scaledependent anisotropy. We discuss that the observed anisotropy is consistent with k ∝ kwhere k and k ⊥ are wave numbers parallel and perpendicular to (local) mean magnetic field, respectively.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
238
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(266 citation statements)
references
References 17 publications
(31 reference statements)
27
238
1
Order By: Relevance
“…Its linear modes are the whistler waves with ω ± = ±k d i k ⊥ . Some key properties of the EMHD turbulence have been investigated both numerically and theoretically, suggesting that the Kolmogorov type arguments work fine (Biskamp et al 1999;Ng et al 2003;Cho & Lazarian 2004. A calculation along the lines of the one below for KAWs, shows that the energy spectrum for whistler wave turbulence is…”
Section: Two-fluid Plasma Dynamicsmentioning
confidence: 99%
“…Its linear modes are the whistler waves with ω ± = ±k d i k ⊥ . Some key properties of the EMHD turbulence have been investigated both numerically and theoretically, suggesting that the Kolmogorov type arguments work fine (Biskamp et al 1999;Ng et al 2003;Cho & Lazarian 2004. A calculation along the lines of the one below for KAWs, shows that the energy spectrum for whistler wave turbulence is…”
Section: Two-fluid Plasma Dynamicsmentioning
confidence: 99%
“…As with the MHD scale cascade, there are a number of observational and theoretical works, which identify turbulent fluctuations at small scales as having properties of linear wave modes (e.g., Denskat et al 1983;Goldstein et al 1994;Ghosh et al 1996;Biskamp et al 1996Biskamp et al , 1999Leamon et al 1998;Cho and Lazarian 2004;Bale et al 2005;Galtier 2006;Sahraoui et al 2010Howes et al 2006Howes et al , 2008Howes et al , 2012bSchekochihin et al 2009;Gary and Smith 2009;Chandran et al 2009;Chen et al 2010bChen et al , 2013a. A recent analysis by Chen et al (2013c) showed that the ratio of density to magnetic fluctuations in the range between ion and electron scales is very close to that expected for kinetic Alfvén waves, and not whistler waves, and concluded that the fluctuations in this range are predominantly strong kinetic Alfvén turbulence.…”
Section: Ion Scale Instabilities Driven By Solar Wind Expansion and Cmentioning
confidence: 99%
“…We found no evidence, in either 2D or 3D, of a dissipative cutoff, implying that the Hall term is able to dominate on all scales and that the coupling is nonlocal in Fourier space. Additional evidence of the nonlocal nature of the Hall cascade comes from the strong anisotropy in the presence of a uniform field found by ourselves and others (Cho & Lazarian 2004, 2009; if the coupling were purely local in Fourier space, then including a uniform field would have no effect at all on small scales, in contrast to what is observed.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 71%
“…None of the fully nonlinear calculations, of ourselves or numerous other authors (Biskamp et al 1996(Biskamp et al , 1999Dastgeer et al 2000;Dastgeer & Zank 2003;Cho & Lazarian 2004;Shaikh & Zank 2005;Cho & Lazarian 2009), which have a broad variety of different initial conditions including sufficiently strong magnetic fields, have ever found anything other than a standard Hall cascade. Cumming et al (2004) also consider the possibility of a Hall instability, and its relevance for the evolution of neutron star magnetic fields.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation